Effect of palmitic and oleic acid mixture on performance and emission analysis of a di diesel engine. (2021) - Bibin, Chidambaranathan; Devan, P.K.; Senthil Kumar, S.; Gopinath, S.; Sheeja, R.; Ashok, K.G.
Abstract: The methyl ester is a sustainable, biodegradable and non-toxic fuel. Vegetable oil can be converted to methyl ester through a process of transesterification. Very a few works have been published in the literature on the use of two different methyl esters in the blended form of diesel fuel. In the present work, however, two methyl esters, namely PME and MME, were chosen and used as fuel in the blended form. Palmitic and oleic acids are the main fatty acid composition of methyl esters. The existence of a single bond of oleic acid in methyl esters can improve the combustion characteristics. Empirical studies on diesel engine reveal that there is a reduction in brake thermal efficiency (BTE) and an increase in NOx emissions and CO2 emissions with an increase in the concentration of methyl ester in the blend. However, the emissions such as Smoke, CO and UHC were reduced significantly. At rated power, Brake thermal efficiency values of standard Diesel, and blends B20, B40, B60 and B80 are 29.1%, 28.5%, 28%, 27.4%, and 26.9% respectively. The NOx emissions are in the order of 1515 ppm, 1546 ppm, 1552 ppm, 1566 ppm and 1630 ppm and smoke emission are 4.4 BSU for diesel fuel whereas it decreased with the increase of methyl ester in the blends. The same trend has been observed for hydrocarbon emissions. The study reveals that the B20 blend (80% Diesel + 10% Pongamia Methyl Ester + 10% Mahua Methyl Ester) is similar to that of diesel fuel in terms of performance and oxides of nitrogen emission.